Law Vs Letter. The Evolution of the Cain Figure in US Literature: Transcending Moral Censorship? - Claude Le Fustec (Revue LISA)
As the law breaker, Cain appears as ideally situated to examine the issue of moral censorship. The United States, with its stern history of authoritarian Puritanism, offers a perfect locus for the study of censorship. Thus, the analysis of the evolution of the Cain figure in the literature of the United States cannot but provide a unique viewpoint on the tricky issue of this powerful western country’s evolving stance toward law and authority. Focusing on three American novels from different periods, The Scarlet Letter (1850), East of Eden (1952), and Sula (1973), this study hopes to expose the complexification of the traditional Christian reading of the evil transgressor. In a post-Christian age, Cain has stopped being censured. This means no mere axiological inversion but a complexification of moral matters paradoxically raising fundamental ontological questions in a world supposedly devoid of transcendence. Through the characters of Hester, Caleb and Sula and the evolution from one to the other as specific Cain figures, one may perceive a whole society’s ideological metamorphosis with respect to normative moral thinking.